Cross-cultural Differences of Stereotypes about Non-verbal Communication of Russian and Chinese Students - I A Novikova; M V Gridunova (Peoples' Friendship University of Russia (RUDN University), 2011)
The article deals with peculiarities of non-verbal communication as a factor of cross-cultural intercourse and adaptation of representatives of different cultures. The possibility of studying of ethnic stereotypes concerning non-verbal communication is considered. The results of empiric research of stereotypes about non-verbal communication of Russian and Chinese students are presented.